The Effect of Weathered Layer Thickness and Slope on Potential Areas of Landslides in Gerbosari Village, Samigaluh District, Kulonprogo Regency, Indonesia - Novia Nurul Khayati; Sudarmaji; Eddy Hartantyo (UIR PRESS, 2022)
Gerbosari Village has a history of landslides with intensity and risk of 56 occurrences over 5 years. Gerbosari Village, Samigaluh District, Kulonprogo Regency is located at geographic coordinates 7◦ 38 '45.33